Functional asymmetry of lower limbs: A study of “Palthi” posture among Khattris of Lucknow - Tandon, Vinod Kumar (Anthropological Review, 1987)
The way of taking the Palthi position (sitting with crossed legs) was investigated in a group of 185 righthanded and IS lefthanded subjects. According to the author, the tendencies to place the left leg over the right one or vice versa are associated with the functional asymmetiy of the celebral cortex.